PENGARUH KEMASAN, HARGA, KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN BERULANG MIXUE SEMARANG - Nadia Ayu Majiid; Rudi Kurniawan; Mahmud; Suhita Whini Setyahun (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
The food and beverage business is currently experiencing significant development, many businesses are innovating and developing. The many interesting innovations mean that foreign products are believed to have superior quality, especially in beverage products, many outlets have emerged so there is very tight competition. One of the ice cream products that is currently popular is Mixue ice cream & Tea. This research aims to test and analyze the influence of packaging, price and service quality on repeat purchase decisions of Ice Cream & Tea consumers. The research sample was taken as many as 120 respondents, with data collection methods via Google online forms. This research uses quantitative research. The sampling technique was non-probability sampling, namely purposive sampling, determining the criteria for respondents to be consumers of Mixue Ice Cream & Tea Kota Semarang, aged 17 to 35 years, and had made a minimum of five purchases of Mixue Ice Cream & Tea products. The analysis used is SEM-PLS, with the Smart PLS 4 application as a data analysis instrument. This research has results, namely that packaging, price, purchasing, service quality have a significant influence.